Association of fermented food intake with the prevalence of depressive symptoms and suicidal ideation in men and women stratified by age: the Korea National Health and Nutrition Examination Survey 2014–2022 - Kim, Taehoon; Park, Yongsoon (Frontiers in Nutrition, 2026)
IntroductionAssociations between fermented foods and the risk of depression and suicidal ideation have been suggested; however, the effects of fermented food types and sex-specific differences remain unknown. The present study investigated the hypothesis that the association of fermented food intake and types with the prevalence of depressive symptoms and suicidal ideation differs between men and women. Age-related interactions were evaluated for the association.MethodsUsing data from the Korea National Health and Nutrition Examination Survey 2014–2022, 8,747 men and 12,449 women aged 19–79 years were analyzed. Depressive symptoms were defined as a Patient Health Questionnaire-9 (PHQ-9) score ≥10 and suicidal ideation as a score ≥1 on the ninth question of PHQ-9.ResultsThe intake of fermented foods, soy products, and vegetables was inversely associated with the prevalence of depressive symptoms and suicidal ideation in the total population. The prevalence of depressive symptoms was inversely associated with the intake of fermented soy products and vegetables in women and with the intake of fermented dairy products in men. Additionally, the prevalence of suicidal ideation was inversely associated with fermented soy product intake in women. A significant age-related interaction was observed between fermented soy products and prevalence of depressive symptoms in women.ConclusionThe intake of fermented foods was inversely associated with the prevalence of depressive symptoms and suicidal ideation with sex-specific differences, suggesting that fermented foods could be beneficial for preventing depressive symptoms and suicidal ideation in Korean adults.